Statistical physics-based analysis of the adsorption of Cu2+ and Zn2+ onto synthetic cancrinite in single-compound and binary systems. Issue 4 (August 2019) - Selim, Ali Q.; Sellaoui, Lotfi; Ahmed, Sayed A.; Mobarak, Mohamed; Mohamed, Essam A.; Lamine, Abdelmottaleb Ben; Erto, Alessandro; Bonilla-Petriciolet, Adrián; Seliem, Moaaz K.
Highlights: Copper and zinc ions adsorption kinetics and isotherms on cancrinite were studied. Metal adsorption isotherms were investigated in single and binary systems. Statistical physics models were used to understand the adsorption mechanism. Adsorption thermodynamic parameters were calculated and interpreted. Abstract: Adsorption isotherms of Cu 2+ and Zn 2+ onto cancrinite were investigated in single-compound and binary systems at pH 6.0 and room temperature. The maximum adsorption capacity of Cu 2+ was higher than Zn 2+ in both the systems. This result could be related to Pauling electronegativity and hydrated ionic radius of these metals, making the cancrinite more selective for Cu 2+ than Zn 2 . The separation factor ( α C u, Z n ) was greater than unity confirming the higher selectivity for Cu 2+ adsorption. Langmuir and Freundlich models fitted well the single-compound adsorption isotherms. In order to obtain a better interpretation of the adsorption of Cu 2+ and Zn 2+ in single and binary systems, a monolayer and an exclusive extended monolayer models were adopted. According to these statistical physics models results, the receptor sites of cancrinite showed to be more selective for Cu 2+ ( n = 0.94) than Zn 2+ ( n = 0.77) in single-compound systems. Due to the competitive effect arising between Cu 2+ and Zn 2+ on the same receptor site, the n values were reduced in binary system to 0.68 and 0.39 for Cu 2+ and Zn 2+, respectively. Furthermore, the adsorption energies in single-compound systems were equal to 23.78 and 19.23 kJ/mol for Cu 2+ and Zn 2+, respectively. In binary system, the adsorption energies of the studied ions decreased and their values in all the systems indicated the existence of a physisorption process. The reduction of the adsorbed capacity ratio between the binary and single-compound systems (i.e. Qb /Qs ) highlighted the antagonistic effect between copper and zinc ions. Finally, thermodynamic parameters were investigated in detail.